Study of mesomorphism, thermotropic properties and pitch in new chiral smectogenic imine compounds - Nesrullajev, Arif; Eran, Belkis Bilgin (ELSEVIER, 2015)
We report the thermotropic, thermo-morphologic and structural properties of four homologs of (S)-5-alkyloxy-2-[{4-(2-methylbutoxy)phenylimino}methyl]phenol liquid crystalline salicylaldimine compounds, which are firstly synthesized by our group. These compounds are monomorphic mesogens and exhibit the enantiotropic chiral smectic C* mesophase (SmC*). Typical textures of the SmC* mesophase and crystalline state of these new salicylaldimine compounds in large temperature intervals and in heterophase regions of the direct and reverse phase transitions have been investigated in detail. Temperature dependences of the pitch of chiral structure of the SmC* mesophase and the space period of chiral structure for both heating and cooling processes have been determined. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Liquid crystals; Salicylaldimine compounds; Smectic C*; Chiral structure; Phase transitions; Pitch of chiral structure; ANTIFERROELECTRIC LIQUID-CRYSTALS; PHASE-TRANSITIONS; HELICAL PITCH; THERMAL HYSTERESIS; CHAIN-LENGTH; COMPLEXES; SALICYLALDIMINE; COPPER(II); SERIES; ORDER; Chemistry; Physics